The impact of Product Modification on Customer Satisfaction. - Vannarajah, T.L.; Jude Leon, S.A. (South Eastern University of Sri Lanka, 2011)
This research concerns with the analysis of "The impact of product modification on customer satisfaction". The researcher formulated problem question as "Does product modification have significant influence on customer satisfaction?" The following objectives are drawn for this valuable study such as to identify the relationship between product modification and customer satisfaction, to measure the impact of product modification on customer satisfaction, to identify the factors influencing on customer satisfaction and to identify the features of cellular phone, in which modification may be occurred. Some limitations were also identified in this research, such as the respondents were selected only from Jaffna peninsula, this study relates with behavioral patterns, so it may be changed from period to period, only primary data were used by the researcher, there are number of companies are being in the cellular phone industry, but in this research only two companies, such as Nokia and Sony Ericsson were taken in to account. In this research, fifty customers were identified as sample. Data were collected from selected customers through questionnaires and these data were presented and analyzed by using statically tools. The results of these analyses were used to test the relationship between product modification and customer satisfaction. Here, five hypotheses were conducted as the higher the product modification will lead to higher the customer satisfaction, desirable size and color of the phone may increase the level of customer satisfaction, convenient phone design leads to high satisfaction, changes in the product features, which directly affect the customer satisfaction and there is no relationship between product modification and customer satisfaction. The research findings indicate the relationship between product modification and customer satisfaction as positive at the r point of 0.793(**) and has significant impact on customer satisfaction at the regression point (r2) of0.629 with the significant level of 0.000. From these findings, we can conclude that "there is a high positive relationship between product modification and customer satisfaction". And "all product modification variables have significant influence on customer satisfaction".
Keywords: Product Modification; Customer saisfaction